Factors Influencing The Adoption And Use Of Mobile Money In Cameroon: Case Of Mobile Money Operators And Users In Buea - Wantchami, Nengieh Lizzie; Ngange, Kingsley Lyonga; Senge, Hallepie Barbara; Oscar, Lingongo; Ebude, Akame (Advances in Social Sciences Research Journal, 2021)
Mobile Money is an innovation that has transformed e-business in the Cameroonian context. This study examines the factors that enhance the adoption and use of mobile money in Buea, capital of the South West Region of Cameroon. The theoretical framework used is the diffusion of innovation. The qualitative approach is adopted, with 10 mobile money operators and 10 mobile money users interviewed using a structured interview protocol. Results show that participants prefer adopting and using mobile services because they are easy to use, convenient, readily accessible, and have less charges compared to the traditional banking system. Telecommunications companies should therefore, continue to consider less charges and bonuses as a strategy to increase penetration and adoption of mobile money services. Likewise, the instructions and language essential to effect Mobile Money operations like internet and airtime purchase should remain simple.